(untitled) (Raparin Journal of Humanities (RJH), 2021)
Praise be to God, and may blessings and peace be upon the Messenger of God, and upon his family, companions, nation, and those who follow him. And yet: This research talks about the difference of religion that has a great impact in changing the legal rulings and in many issues, the Muslim must observe them and commit to applying them because they affect his worldly and eschatological life, and he must know well what he has and what he owes towards a non-Muslim, especially if he lives with him and next to him,to follow the legitimate path,and approach moderation in dealing with it. The importance of the research lies in explaining the rulings on dealing with non-Muslims, especially in this era in which there has been a lot of mixing of Muslims with others in terms of the large number of Muslims coming and refugees to non-Muslim countries, and the number of non-Muslims arriving, residents, merchants and workers to Muslim countries, and the effect of this difference in religion on many changes Among the legal rulings, mixing a Muslim with others was not new, rather it was present since the early ages of Islam. So is a non-Muslim with whom a Muslim lives or deals with him in Muslim countries the same as dealing himself with a Muslim? Is there a difference between non-Muslims themselves in the consideration of Islam? Is there a differentiation between the polytheist and the apostate, and between the people of the Book from the Jews and the Christians, especially when coexisting with them, whether that is by marrying someone who contradicts them in religion or treatment, or through inheritance, or other than all these questions are referred to in this research from the Islamic view and rulings Legitimacy is strengthened and based on evidence from the recognized texts and the approved sayings of the jurists,Because we desperately need to know these rulings today and stand on the limits set by God Almighty and on numerous and different issues, and for this reason this research can be considered one of the contemporary jurisprudential topics, because the coexistence of a Muslim with others has become one of the issues that have spread widely between us and our young men and women, which is what It prompted me to write a study on the effect of the difference in religion in changing many of the legal rulings at that time.